REALITAS ERA VICTORIA DALAM CERPEN â€œNELAYAN DAN JIWANYAâ€ KARYA OSCAR WILDE: KAJIAN HERMENEUTIKA GADAMER* (Reality of Victorian Era in Oscar Wildeâ€™s Short Story: â€œNelayan dan Jiwanyaâ€: Gadamerâ€™s Hermeneutics Study) - Wicaksana, Wildan Ilham (Balai Bahasa Jawa Tengah, 2019)
The purpose of this study is to find out reality and morality in Oscar Wilde?s short story entitled Nelayan dan Jiwanya (?NdJ?) written by Oscar Wilde. This study applied Gadamer?s hermeneutics approach. The hermeuneutic procedure of Gadamer?s is dialogic involving historicity and prejudice. Hermeneutics is an interpretative concept towards symbols, traditions, actions, texts, and other forms of concrete materials. The method established in this study is a qualitative descriptive one. It lead the researcher to describing the background of the historical text and the author?s prejudice. The result of this study shows that the description of reality and morality in the Victorian Era, for instance women style or fashion and life, religion issues and atheism, poverty and slavery. Keywords: hermeneutics, gadamer, victorian